The influence of Zinc, Selenium and Iodine on dietary supplementation in people with Hypothyroidism (Research, Society and Development, 2021)
The present study aimed to identify the influence of zinc, selenium and iodine in the control of subclinical hypothyroidism and their descriptions in the scientific literature, which have a great potential for innovation and have not yet been fully explored. A literature review was carried out, in which it adopts a replicable, scientific and transparent process, being recommended to gather and analyze relevant studies on the subject. Five scientific databases were used in the research, ScienceDirect Journals (Elsevier), Directory of Open Access Journals (DOAJ), PMC (PubMed Central), MEDLINE/PubMed (NLM) and Scielo. The indexing terms were used in the English language “hypothyroidism” and “food”. As inclusion criteria, articles that had one of the indexing terms in the title and/or abstract and/or keywords, published in the last 5 years, were used. After searching the databases, 70 articles were identified and after the filtering and selection procedure resulted in 19 articles selected for the present study. A proper and balanced diet can also become an important factor in adjusting the proper functioning of the thyroid gland (TG). It was observed that minerals, zinc, selenium and iodine, are important for the maintenance of the organism and for the production of thyroid hormones, with this the amounts of these components in the body must always be balanced.